Review on 40 Pins Microcontroller 8051 - Dukale, Prachi; Lad, Sanjana; Merchant, Taskeen; Rane, Gaurav; Qureshi, Aman; Khan, Abdul Ahad; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
A microcontroller can be considered a self -contained system with a processor ,memory and peripherals and can be used as an embedded system .The majority of microcontrollers in use today are embedded in other machinery, such as automobiles , telephones , appliances and peripherals for computer systems .Mixed signal microcontrollers are common integrating analog components needed to control non digital systems In the context in the internet of things, microcontrollers are economical and popular means of data collection, sensing and actuating the physical world as edge devices.